80.2k views
4 votes
Y = -x + 4 , y = -3x + 16 . Answer as an ordered pair. (x,y)

User Cramopy
by
4.0k points

2 Answers

5 votes
Set them equal to each other. -x + 4 = -3x + 16 >>> (-x+3x)=(16-4) >>> 2x= 12 so x =6. Plug in x to an equation. Y= -(6) + 4 so y = -2. (6,-2) is the answer.
User Patrick Wright
by
4.9k points
6 votes

Answer: Answer is (-3, 7)

Explanation:

y = -x + 4 equ 1

y = 3x + 16 equ 2

Make x subject of formular in equ 1

x = 4 - y equ 3

Subatitute x = 4 - y in equ 2

y = 3(4-y) +16

y = 12 - 3y + 16

y + 3y = 12 + 16

4y = 28

y = 28/4 = 7

Substitute y = 7 in equ 1

7 = -x + 4

7 - 4 = -x

x = -3

Answer is (-3, 7)

User Richard Burton
by
4.8k points